Electroacupuncture Improves M2 Microglia Polarization and Glia Anti-inflammation of Hippocampus in Alzheimer’s Disease - Xie, Lushuang; Liu, Yi; Zhang, Ning; Li, Chenyu; Sandhu, Aaron F.; Williams, George; Shen, Yan; Li, Hongying; Wu, Qiaofeng; Yu, Shuguang (Frontiers in Neuroscience, 2021)
Background: Alzheimer’s disease (AD) is a neurodegenerative disease characterized by loss of recognition and memory. Neuroinflammation plays pivotal roles in the pathology of AD and affects the progression of the disease. Astrocyte and microglia, as main immune executors in the central nervous system (CNS), participate into the inflammatory response in AD. Glia polarize into different phenotypes during neurodegeneration. Pro-inflammatory glia produce cytokines (IL-1β, TNF-α, and IL-6) resulting into debris aggregates and neurotoxicity. Anti-inflammatory phenotypes produce cytokines (IL-4 and IL-10) to release the inflammation. Electroacupuncture is a useful treatment that has been found to slow the neurodegeneration in animals through experimentation and in humans through clinical trials. The aim of this study was to uncover the mechanisms of glia activation, microglia polarization, and cytokine secretion regulated by electroacupuncture as a treatment for AD. Methods: Twenty male Sprague–Dawley (SD) rats were randomly divided into four groups: Control group (Control), Normal saline group (NS), AD group (AD), and Electroacupuncture group (Acupuncture). The AD and Acupuncture groups were bilaterally injected with Aβ1–42 into the CA1 field of the hippocampus. The Acupuncture group received electroacupuncture stimulation on the acupoint “Baihui” (GV20) for 6 days per week for a total of 3 weeks. The Morris Water Maze (MWM) was used to evaluate learning and memory capacity. Immunofluorescence was used to stain GFAP and Iba1 of the DG and CA1 in the hippocampus, which, respectively, expressed the activation of astrocyte and microglia. The M1 microglia marker, inducible nitric oxide synthase (iNOS), and M2 marker Arginase 1 (Arg1) were used to analyze the polarization of microglia. The pro-inflammatory cytokines (IL-1β, TNF-α, and IL-6), anti-inflammatory cytokines (IL-4 and IL-10), and pathway-molecules (p65 and Stat6) were tested to analyze the glia inflammatory response by immunofluorescence and polymerase chain reaction (PCR). Results: The MWM results showed that electroacupuncture improves the escape latency time and the swimming distance of AD rats. The number of GFAP and Iba1 cells significantly increased in AD rats, but electroacupuncture decreased the cells. The iNOS-positive cells were significantly increased in AD, and electroacupuncture decreased the positive cells. Electroacupuncture elevated Arg1-positive cells in AD rats. Electroacupuncture decreased the glia pro-inflammatory cytokine expression and increased the anti-inflammatory cytokine expression in AD rats. Furthermore, electroacupuncture inhibited the NF-κB pathway molecule (p65) while raising the Stat6 pathway molecule (Stat6). Conclusion: These results provide evidence that electroacupuncture improves the recognition abilities and memory of AD rats. Electroacupuncture inhibits the activation of glia and polarizes microglia toward the M2 phenotype. Electroacupuncture decreased the pro-inflammatory cytokines (IL-1β, TNF-α, and IL-6) and increased the anti-inflammatory cytokines (IL-4 and IL-10). Furthermore, electroacupuncture affects the immune responses through inhibition of NF-κB pathway but activation of Stat6 pathway.